A Conversation About Writing and Citing with Justice and Charity - Glennan, Stuart; Russo, Federica (KULA)

(untitled) (University of Victoria Libraries, 2026)
Citational injustice often refers to the underrepresentation or misrepresentation of the work of members of marginalized populations within academic publications. The literature emphasises how these unjust practices reproduce and perpetuate known hierarchies and colonial power structures. While these are global trends that impact all academic disciplines, a full understanding of them requires considering how these practices play out within specific disciplinary contexts. In this conversation, Stuart Glennan and Federica Russo draw on their experiences as philosophers of science in the Global North to reflect on sources of citational injustice in their field. The conversation highlights how technologies have changed norms and habits regarding citational practices and points to charity as a key value to foster just practices, both in author and in reviewer roles. The authors consider how a path to more just citational practices may hinge on reconceiving what counts as a “good” philosophy paper.